Opportunities and Challenges for Successful Use of Bevacizumab in Pediatrics - Barone, Amy; Rubin, Joshua B. (Frontiers in Oncology, 2013)
Bevacizumab (Avastin) has rapidly gained status as a broadly active agent for malignancies of several different histologies in adults. This activity has spawned a range of uses in pediatrics for both oncologic and non-oncologic indications. Early analyses indicate that pediatric cancers exhibit a spectrum of responses to bevacizumab that suggest its activity may be more limited than in adult oncology. Most exciting, is that for low-grade tumors that threaten vision and hearing, there is not only evidence for objective tumor response but for recovery of lost function as well. In addition to oncological indications, there is a range of uses for non-oncologic disease for which bevacizumab has clear activity. Finally, a number of mechanisms have been identified as contributing to bevacizumab resistance in cancer. Elucidating these mechanisms will guide the development of future clinical trials of bevacizumab in pediatric oncology.